Microparticle-Based Controlled Drug Delivery Systems: From Experiments to Statistical Analysis and Design - Lotter, Sebastian; Bellmann, Tom; Marx, Sophie; Wesinger, Mara; Brand, Lukas; Schäfer, Maximilian; Fischer, Dagmar; Schober, Robert (Proceedings - IEEE Global Communications Conference, GLOBECOM, 2023)
Controlled drug delivery (CDD), the controlled release and delivery of therapeutic drugs inside the human body, is a promising approach to increase the efficacy of drug administration and reduce harmful side effects to the body. CDD has been a major research focus in the field of molecular communications (MC) with the goal to aid the design and optimization of CDD systems with communication theoretical analysis. However, the existing studies of CDD under the MC framework are purely theoretical, and the potential of MC for the development of practical CDD applications remains yet to be shown. This paper presents a step towards filling this research gap. Specifically, we present a novel MC-based model for a specific CDD system in which drugs are embedded into microparticles and released gradually towards the target site. It is demonstrated that the proposed model is able to faithfully reproduce experimental data. Furthermore, statistical analysis is conducted to explore the impact of the microparticle size on the drug release. The presented results reveal the sensitivity of the drug release to changes in the microparticle size. In this way, the proposed model can be used for the design of future microparticle-based CDD systems.
Created from Fastlane, Scopus look-up